Determining Factors Influencing Interest in Using Paper Packaging Among Indonesian Customers: A Sustainable Consumer Behaviour Approach - Setiawan, Rizal Justian; Astini, Rina; Pujiwati, Ami; Ma'ruf, Khakam; Azizah, Nur; Rusmala, Amna; Sofie, Viola Indriana; Khosyiati, Nur Evirda (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: To analyze the determining factors influencing Indonesian consumers’ interest in using paper-based food packaging. In the context of increasing plastic waste and rising environmental concerns, the study seeks to evaluate behavioral tendencies supporting sustainable consumer practices aligned with sustainable goals. Methodology: A quantitative approach using an online questionnaire with a purposive sample of 710 respondents across Indonesia. The data were analyzed using IBM SPSS and Artificial Neural Network (ANN) models to explore complex relationships between sustainable consumer behavior (SCB) variable with attitude (AT), environmental insight (EI), environmental risk perception (ERP), governmental support & regulations (GSR), intention (IN), perceived behavioral control (PBC), and subjective norm (SN). Results: The survey results processed with ANN showed a high level of accuracy for all hypothesized relationships, with AT emerging as the most influential factor on SCB (97.75% accuracy), followed by PBC and IN. All seven tested hypotheses were positively accepted. Findings: Consumers’ positive attitudes significantly influence their sustainable consumption choices in the context of preference for paper packaging over plastic packaging, indicating a shift towards environmentally responsible behavior. Novelty: This study uniquely integrates ANN into behavioral research on sustainability, offering a more precise modeling of consumer intentions and patterns compared to traditional statistical methods. Originality: Unlike previous studies focused on general consumer habits, this research considers packaging material choices to present a comprehensive model of sustainable behavior in a developing country context, emphasizing behavioral modeling over object detection or vision-based methods. Conclusion: This study underscores the need to promote positive attitudes and awareness of negative environmental impacts when using plastic packaging to encourage sustainable consumer behavior. Paper packaging can be alternative strategies to reduce plastic waste. Type of Paper: Empirical research paper.